2020
DOI: 10.1080/07391102.2020.1841028
|View full text |Cite
|
Sign up to set email alerts
|

Anin-silicoanalysis of ivermectin interaction with potential SARS-CoV-2 targets and host nuclear importin α

Abstract: Ivermectin (IVM) is a broad-spectrum antiparasitic agent, having inhibitory potential against wide range of viral infections. It has also been found to hamper SARS-CoV-2 replication in vitro, and its precise mechanism of action against SARS-CoV-2 is yet to be understood. IVM is known to interact with host importin (IMP)α directly and averts interaction with IMPβ1, leading to the prevention of nuclear localization signal (NLS) recognition. Therefore, the current study seeks to employ mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
38
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 59 publications
5
38
1
3
Order By: Relevance
“…This stable conformation of IVM at the protein-protein interface suggests that the inhibitory activity of IVM could occur by inhibiting the dimerization of Nsp9 replicase since dimer formation has been related to the enhancement of nucleic acid binding and viral replication (Qiu & Xu, 2020 ). Some of the interactions present in the docked Nsp9-IVM complex (Pro6 and Gly100) were also identified in a previous theoretical study (Azam et al, 2020 ).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…This stable conformation of IVM at the protein-protein interface suggests that the inhibitory activity of IVM could occur by inhibiting the dimerization of Nsp9 replicase since dimer formation has been related to the enhancement of nucleic acid binding and viral replication (Qiu & Xu, 2020 ). Some of the interactions present in the docked Nsp9-IVM complex (Pro6 and Gly100) were also identified in a previous theoretical study (Azam et al, 2020 ).…”
Section: Resultssupporting
confidence: 66%
“…Recently, computational studies employed docking and molecular dynamics (MD) simulations to explore the ability of IVM to inhibit mouse importin-α (PDB entry 5FC8) and several SARS-CoV-2 targets. They found that IVM binds to importin-α with moderate affinity and Nsp9 with the highest affinity among several COVID-19 targets (Azam et al, 2020 ). Another recent study employed docking and MD simulations with the molecular mechanics Poisson-Boltzmann surface area (MMGBSA) approach to explore the affinity of IVM with importin-α and several SARS-CoV-2 targets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In computer-aided drug discovery projects, several docking programs are routinely employed for interpreting the binding mode and the affinity of a ligand relative to a protein. However, the binding energy predicted by docking algorithms cannot be relied and hence, it is imperative to employ post-docking analyses to avoid false negatives and false positives [44] Nowadays, MM-GBSA method is frequently used for predicting the accurate binding energy of a protein-ligand complex and the obtained results can be exploited more rationally in the design of drug candidates. [ 45 , 46 ] Therefore, the top ten poses of SARS CoV-2 main protease–teicoplanin complexes obtained from hundred docking runs in each category were further analysed by MM-GBSA approach for prediction of more accurate binding energy.…”
Section: Resultsmentioning
confidence: 99%
“…13 17 In a vertiginous search for COVID-19 treatments, Caly et al conducted an in vitro exploration that showed ivermectin's inhibitor role on the replication of the SARS-CoV-2 virus, 17 18 among few other in silico and in vitro results suggesting the same. [19][20][21] Thus, a considerable amount of preprints and protocol records quickly appeared, reporting the clinical efficacy of ivermectin in standard doses for COVID-19. The dissemination of these results caused confusion, and the general population and some clinicians endorsed the use of ivermectin, especially in Latin America.…”
mentioning
confidence: 99%